2021
DOI: 10.31674/mjn.2021.v12i03.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Self-Care Program for Patients Using Colostomy at Mansoura City

Abstract: Background: Colostomy means an artificial opening of the colon onto the abdominal surface. It may originate from: The sigmoid colon, the descending colon, the transverse colon or the ascending colon. the colostomy need care so that the patients can determine self-care to prevent complications. Aim: Evaluate effect of self-care program for patients using colostomy at Mansoura City. Design: A quasi-experimental research design. Setting: Conducted at the Surgical Outpatients Clinic in Mansoura University Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The great majority of people were illiterate, and an even larger proportion did not get sufficient formal instruction, which would have helped them become more knowledgeable about the problem. This conclusion is consistent with that of Sabea and Shaqueer (2021), who reported that the participants' understanding of colostomy selfcare was inadequate.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The great majority of people were illiterate, and an even larger proportion did not get sufficient formal instruction, which would have helped them become more knowledgeable about the problem. This conclusion is consistent with that of Sabea and Shaqueer (2021), who reported that the participants' understanding of colostomy selfcare was inadequate.…”
Section: Resultssupporting
confidence: 91%
“…In addition, the findings of Qalawa and Moussa (2019), who discovered that the majority of patients (73.1 percent) came from rural areas, provide weight to these findings. despite the fact that I disagree with Sabea and Shaqueer (2021), who found that the vast majority of patients (60%) lived in urban areas. It is conceivable to draw the conclusion that the patients' knowledge of colostomy self-care was inadequate based on the data shown in summary table (2) as well as on the data presented in an overall evaluation table (3).…”
Section: Resultsmentioning
confidence: 73%
“…Consideration of participants’ background characteristics, such as education level and marital status, is crucial during the implementation of the education program to improve self-care abilities for patients with intestinal stomas. This importance arises from the association of educational level and marital status with self-care knowledge, which has been supported by studies conducted by Ran et al ( 2016 ) and Sabea and Shaqueer ( 2021 ). To maximize the effectiveness of the education program to improve self-care abilities for patients with intestinal stomas, it is recommended to include periodic repetitions of the education sessions as suggested by Ran et al ( 2016 ) and supported by the research conducted by Sabea and Shaqueer ( 2021 ).…”
Section: Discussionmentioning
confidence: 74%
“…As a result, there is a clear need to establish an education program with the objective of enhancing patients’ knowledge in this area. To develop an effective program, it is essential to conduct an analysis of the specific requirements of actual patients (Sabea & Shaqueer, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation